Phnom Penh Lullaby - Kloc, Paweł (Kloc, Paweł, 2011)
Verzio9 FF Submission. Duration: 01:38:00 Saran and Ilan Schickman are an unlikely couple in Phnom Penh. She is an alcoholic Cambodian, and he an Israeli who moved to Phnom Penh looking for a better life. It quickly becomes clear that their relationship is extremely problematic. They don't speak one another's language, nor do they possess enough money or affection to raise their young daughters Marie and Jasmine properly. She wants to get married and go to Israel, but he wants a new life, love and acceptance. Slowly but surely the parents' heartbreaking quarrels tear the family apart in front of the camera. Saran's parents are worried that the children will be sold to a foreigner, and Ilan also begins to be increasingly suspicious of his partner. Meanwhile, they are forced to survive on the margins of society - Ilan tries to earn some money by reading tarot cards to tourists in the city's red light district. Phnom Penh Lullaby portrays people trapped in their lives, dreaming of happiness but prevented from reaching it by forces they cannot control.